1998
DOI: 10.1021/ja9739603
|View full text |Cite
|
Sign up to set email alerts
|

Spin Density Maps in the Triplet Ground State of [Cu2(t-Bupy)4(N3)2](ClO4)2 (t-Bupy = p-tert-butylpyridine):  A Polarized Neutron Diffraction Study

Abstract: This paper is devoted to the determination of the spin distribution in the spin triplet ground state of [Cu2(t-Bupy)4(N3)2](ClO4)2, with t-Bupy = p-tert-butylpyridine. The crystal structure, previously solved at room temperature from X-ray diffraction, has been redetermined at 18 K from unpolarized neutron diffraction. The structure consists of binuclear cations in which Cu2+ ions are doubly bridged by azido groups in the 1,1-fashion, and noncoordinated perchlorate anions. The experimental spin distribution ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
135
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 37 publications
13
135
0
2
Order By: Relevance
“…Table 3 bridge. This is in excellent agreement with other reports available in the litterature and compares nicely with data of Polarized Neutron Diffraction (PND) [95,96,109]. The sign alternation of the spin density at the N 1 and N 2 atoms of the azido-bridge is consistent with spin polarization by the bridging nitrogen atoms and it highlights the superexchange pathway between the two magnetic cations.…”
Section: Magnetic Exchange Coupling Constantsupporting
confidence: 91%
“…Table 3 bridge. This is in excellent agreement with other reports available in the litterature and compares nicely with data of Polarized Neutron Diffraction (PND) [95,96,109]. The sign alternation of the spin density at the N 1 and N 2 atoms of the azido-bridge is consistent with spin polarization by the bridging nitrogen atoms and it highlights the superexchange pathway between the two magnetic cations.…”
Section: Magnetic Exchange Coupling Constantsupporting
confidence: 91%
“…[11,22,23] In the early studies, [3][4][5][6][17][18][19][20] the symmetric EO coordination mode behavior seemed intrinsically ferromagnetic and independent of any structural parameters. This is why most previous theoretical studies focused on EO systems to explain such peculiar behavior, [24,[26][27][28][29][30] which was initially attributed to spin polarization effects. [28,30] However, a polarized neutron diffraction study has shown that spin delocalization is indeed the main effect and that spin polarization occurs only within the azido bridge.…”
mentioning
confidence: 99%
“…For an end-on bridging mode, simultaneous pairing of the two paramagnetic centers would lead to ferromagnetic coupling, irrespectively of the q value. Nevertheless, based on polarized neutron diffraction studies, [13] Aebersold et al showed later that a spin-delocalization mechanism in the active-electron approximation must be considered. The coupling would then be ferromagnetic (or antiferromagnetic) under a given q AO value and antiferromagnetic (or ferromagnetic) above, where q AO is the angle for accidental orthogonality.…”
mentioning
confidence: 99%
“…a ferromagnetic coupling occurring in a dimeric m-1,1 azido complex with a q value of 129.38) provides empirical evidence for a positive answer to the question posed by Kahn et al "Can the 1,1-azido group be considered as an almost universal ferromagnetic coupler?". [13] At least, we can say that this assumption must be true for nickel(ii) complexes; nevertheless, MO calculations must be performed to verify that no countercomplementarity effect arises from the long O-P-O and O-W-O bridges connecting the divalent centers. Owing to the lack of available compounds, no clear correlation between q and J for Ni II azido bridged compounds could be found to date.…”
mentioning
confidence: 99%